Greengenes2 unifies microbial data in a single reference tree - McDonald, Daniel; Jiang, Yueyu; Balaban, Metin; Cantrell, Kalen; Zhu, Qiyun; Gonzalez, Antonio; Morton, James T.; Nicolaou, Giorgia; Parks, Donovan H.; Karst, Søren M.; Albertsen, Mads; Hugenholtz, Philip; et al. (Nature biotechnology, 2024)
Studies using 16S rRNA and shotgun metagenomics typically yield different results, usually attributed to PCR amplification biases. We introduce Greengenes2, a reference tree that unifies genomic and 16S rRNA databases in a consistent, integrated resource. By inserting sequences into a whole-genome phylogeny, we show that 16S rRNA and shotgun metagenomic data generated from the same samples agree in principal coordinates space, taxonomy and phenotype effect size when analyzed with the same tree. A comprehensive microbial resource reconciles genomic and 16S rRNA data in a single tree.